In‐Situ Electrostatic Self‐Assembly of Conjugated Polyelectrolytes in a Film. Issue 9 (22nd September 2014) - Lee, Wang‐Eun; Jin, Young‐Jae; Kim, Beomsu Shin‐Il; Kwak, Giseop; Sakaguchi, Toshikazu; Lee, Hyun Hwi; Kim, Joon Heon; Park, Jung Su; Myoung, Nosoung; Lee, Chang‐Lyoul
<x xml:space="preserve">Abstract</x> Localized self‐assembly of conjugated polyelectrolytes (CPEs) in a film is realized by simply contacting the film to appropriate surfactant solutions. This in situ self‐assembly allows simultaneous optical and structural reforming on the selected areas and highly resolved patterning of the CPE film. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>